Fabrication of Metal Nanoparticle Arrays in the ZrO2(Y), HfO2(Y), and GeOx Films by Magnetron Sputtering. (12th July 2017) - Gorshkov, Oleg; Antonov, Ivan; Filatov, Dmitry; Shenina, Maria; Kasatkin, Alexander; Bobrov, Alexander; Koryazhkina, Maria; Korotaeva, Irina; Kudryashov, Mikhail
Abstract : The single sheet arrays of Au nanoparticles (NPs) embedded into the ZrO2 (Y), HfO2 (Y), and GeO x (x ≈ 2 ) films have been fabricated by the alternating deposition of the nanometer-thick dielectric and metal films using Magnetron Sputtering followed by annealing. The structure and optical properties of the NP arrays have been studied, subject to the fabrication technology parameters. The possibility of fabricating dense single sheet Au NP arrays in the matrices listed above with controlled NP sizes (within 1 to 3 nm) and surface density has been demonstrated. A red shift of the plasmonic optical absorption peak in the optical transmission spectra of the nanocomposite films (in the wavelength band of 500 to 650 nm) has been observed. The effect was attributed to the excitation of the collective surface plasmon-polaritons in the dense Au NP arrays. The nanocomposite films fabricated in the present study can find various applications in nanoelectronics (e.g., single electronics, nonvolatile memory devices), integrated optics, and plasmonics.